Life-Cycle Effects on Consumption and Retirement - Hamermesh, Daniel S. (Journal of Labor Economics, 1984)
The effects on consumption and retirement of the length of the horizon are examined. At any given age people will work more and consume less if they expect to live longer. The Terman sample of gifted individuals in 1972 and 1977 is used to relate work status to the length of the horizon, as proxied by parents' longevity. The results suggest the expected positive effect on effort, but its magnitude is quite small. The panel from the Retirement History Survey is used, and effects of the horizon on consumption and retirement jointly are estimated for 1973 and 1975. There is a small positive effect of a more distant horizon (proxied by the number of living parents) on work effort and a stronger but still fairly small negative effect on consumption. Goods and leisure are consumed jointly, suggesting their complementarity in household production, and spending propensities out of social security wealth are far below those out of pension wealth.